Towards capture of dynamic assembly and action of the T3SS at near atomic resolution. (April 2020) - Hu, Jinhong; Worrall, Liam J; Strynadka, Natalie CJ
Highlights: Cryo-EM and cryo-ET are facilitating major advances in our structural understanding of the T3SS. Cryo-EM analyses at near-atomic resolutions have revealed the molecular structures and stoichiometries of the T3SS needle complex components. Cryo-ET structures reveal the overall architecture of the T3SS in its native membrane environment. Multiple structural snapshots captured from a single sample reveal different needle complex assembly states and associated large conformational changes. Sophisticated algorithms and processing approaches allow detailed information to be extracted from cryo-EM and cryo-ET data. Abstract : The T3SS is a syringe-shaped nanomachine essential for the progression of many Gram-negative bacterial infections including plague, typhoid fever, and dysentery. It spans both bacterial membranes and that of the host allowing delivery of proteins that modulate cell function to aid bacterial survival. Its structure has been the focus of scrutiny for 20 years; however, limitations in purification and structure determination techniques have restricted understanding to atomic structures of individual components and subcomplexes or lower resolution information of the more complete assembly. The recent cryo-EM resolution revolution has facilitated dramatic advances in our structural understanding of the T3SS with complimentary techniques of single particle cryo-EM and cryo-ET revealing structures of isolated complexes to near-atomic resolutions or the architecture of the entire T3SS in its native cellular environment. Here we present an overview of these advances and discuss how these structures further understanding of the dynamic process of injectisome assembly.